2006
DOI: 10.1203/01.pdr.0000242262.55324.aa
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride-Sensitive Nasal Potential Difference Is Not Changed by Estradiol and Progesterone Replacement But Relates to BPD or Death in a Randomized Trial on Preterm Infants

Abstract: Postnatal replacement of placental estradiol (E2) and progesterone (P) in preterm infants may improve lung function, possibly mediated through enhanced epithelial Na ϩ transport and alveolar fluid clearance. Preterm infants of Ͻ29 wk gestational age and Ͻ1000 g birth weight requiring mechanical ventilation within 12 h of birth were randomized to receive either 2.5 mg/kg E2 and 22.5 mg/kg P per day (E2/P), or vehicle placebo. Epithelial Na ϩ transport was assessed in 29 infants by measuring total nasal potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…28,29 Moreover, a previous study showed that cultured rat fetal distal lung epithelial cells (FDLE), when switched from fetal (3%) to postnatal (21%) O2 concentration, had increased ENaC mRNA levels and amiloride-sensitive Na + transport. 33 However, in contrast to our results, Thome et al reported that infants at high risk of developing BPD had lower amiloridesensitive nasal potential difference (ASNPD) values in the immediate postnatal period; 13 Gaillard et al reported that at 29 days of age infants with BPD had significantly lower nasal potential difference (N-PD) than those without BPD. 12 The above researchers chose nasal epithelial cells as substitute for alveolar epithelial cells, so the conflicting results with ours may be due to different study methods and cell types.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…28,29 Moreover, a previous study showed that cultured rat fetal distal lung epithelial cells (FDLE), when switched from fetal (3%) to postnatal (21%) O2 concentration, had increased ENaC mRNA levels and amiloride-sensitive Na + transport. 33 However, in contrast to our results, Thome et al reported that infants at high risk of developing BPD had lower amiloridesensitive nasal potential difference (ASNPD) values in the immediate postnatal period; 13 Gaillard et al reported that at 29 days of age infants with BPD had significantly lower nasal potential difference (N-PD) than those without BPD. 12 The above researchers chose nasal epithelial cells as substitute for alveolar epithelial cells, so the conflicting results with ours may be due to different study methods and cell types.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in contrast to our results, Thome et al . reported that infants at high risk of developing BPD had lower amiloride‐sensitive nasal potential difference (ASNPD) values in the immediate postnatal period; 13 Gaillard et al . reported that at 29 days of age infants with BPD had significantly lower nasal potential difference (N‐PD) than those without BPD 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven case-control studies including 4 randomized, placebo-controlled and 7 nonrandomized controlled studies, from the United States, France, German, Swiss, and Finland in last two decades were finally selected per the inclusion criteria. Among these included studies, seven studies were on high altitude pulmonary edema (HAPE) 16 18 19 28 29 30 31 , and the other four studies on respiratory distress syndrome (RDS) 25 27 32 33 . These studies encompassed NPD data obtained with a similar recording procedure: basal level → applied amiloride (100 μM) or Na + -free solution → Cl − free medium and CFTR activator, isoproterenol (10 μM) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%